EatNTrack Malaysia mobile application food calories tracker - a conceptual paper / Maisarah Mohd Saleh ... [et al.] - Mohd Saleh, Maisarah; Abd Rahman, Siti Aishah; Nazarudin, Ainamardia; Abu Kasim, Nurul Ain; Abdul Razak, Fatin Aqilah (2021)
Diet and nutrition apps are among the most popular health and fitness apps used by an increasing number of mobile device users. Undeniably, health and nutrition are some of the valuable aspects of life. With the introduction of mobile computing, health knowledge became much easier to understand due to its mobility and usability. A vast range of smartphone apps is emerging for tracking health and food. However, the existing mobile applications in Malaysia are lacking some important features. To address this limitation, the present mobile application responds by attempting to design and develop a Malaysian mobile nutrition application known as EatNTrack. EatNTrack is a mobile nutrition application that provides crucial features such as the ability to capture the food especially Malaysian foods, scanning food barcode, set the goal and calories of the day, a reminder for the user to capture the food, monthly progress of user, and integration with a wearable device. The needs of these features will give insight into many aspects of a user's eating habits. The more specific and accurate users with reporting, the more accurate their information will be. The aim of the study was to establish an innovative mobile-based dietary awareness tool that could be used to monitor target users' food intake.